Skeletal muscle oxidative stress and inflammation in aging: Focus on antioxidant and anti-inflammatory therapy - Chen, Mingming; Wang, Yiyi; Deng, Shoulong; Lian, Zhengxing; Yu, Kun (Frontiers in Cell and Developmental Biology, 2022)
With aging, the progressive loss of skeletal muscle will have negative effect on multiple physiological parameters, such as exercise, respiration, thermoregulation, and metabolic homeostasis. Accumulating evidence reveals that oxidative stress and inflammation are the main pathological characteristics of skeletal muscle during aging. Here, we focus on aging-related sarcopenia, summarize the relationship between aging and sarcopenia, and elaborate on aging-mediated oxidative stress and oxidative damage in skeletal muscle and its critical role in the occurrence and development of sarcopenia. In addition, we discuss the production of excessive reactive oxygen species in aging skeletal muscle, which reduces the ability of skeletal muscle satellite cells to participate in muscle regeneration, and analyze the potential molecular mechanism of ROS-mediated mitochondrial dysfunction in aging skeletal muscle. Furthermore, we have also paid extensive attention to the possibility and potential regulatory pathways of skeletal muscle aging and oxidative stress mediate inflammation. Finally, in response to the abnormal activity of oxidative stress and inflammation during aging, we summarize several potential antioxidant and anti-inflammatory strategies for the treatment of sarcopenia, which may provide beneficial help for improving sarcopenia during aging.